Interpersonal Communication Komunikasi Antarpribadi Guru Dan Anak Berkebutuhan Khusus (ABK) Tunagrahita Jenjang SMP Dalam Proses Pembentukkan Kepercayaan Diri Di SLB Anugerah Colomadu - Badar Bahaduri, Selya Abyad Setyawa; Hindra H, Nurnawati; Sihabuddin, Sihabuddin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Children with special needs who are mentally retarded are children with below average intellectual abilities. Children with these disabilities of course want to receive an education like children their age. By having interpersonal communication between teachers and students with special needs who are mentally retarded, it makes it easier for teachers to conduct counseling with their students. With this approach through interpersonal communication, five stages of the interpersonal communication process can be carried out which contain the stages of contact, involvement, familiarity, damage and repair to form self-confidence in students with intellectual disabilities. The research method used is a qualitative research method with a descriptive approach. Data collection techniques taken by researchers are through observation, interviews and documentation. The results of this research show that teachers at SLB Anugerah Colomadu can help their students act confidently when meeting new people and have the courage to appear in public, through these five stages of interpersonal communication, self-confidence is achieved in mentally retarded students at the junior high school level at SLB Anugerah Colomadu. Keywords: Interpersonal Communication, Mental Retardation, Teacher, Self-Confidence.